1983
DOI: 10.3109/10799898309041952
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Specific Receptor for Cholecystokinin on Isolated Fundic Glands from Guinea Pig Gastric Mucosa Using a Biologically Active125I-CCK-8 Probe

Abstract: Specific binding sites for cholecystokinin (CCK) have been identified and characterized in fundic glands isolated by collagenase treatment from guinea pig gastric mucosa using a biologically active 125I-labeled derivative of the C-terminal octapeptide of CCK (125IIE-CCK-8). The time course of binding to these glands was rapid, temperature dependent and saturable. At 24, 30 and 37 degrees C, half-maximal binding was reached at 5 min and full binding at 30 min. The addition of a large excess of CCK-8 after 15 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…While there is virtually no information concerning the roles of these hormones in the expression of seasonality of intake in ruminants, CCK, which is secreted in response to ingestion of food and interacts with sensors in the gut wall (Praissman et al 1983) and pancreas (Steigerwalt & Williams, 1981), was found to act as a satiety factor in ruminants (Farningham et al 1993), with its effects being potentiated by central administration of insulin (Riedy et al 1995;Woods et al 1996). Thus, CCK may be involved in the determination of meal pattern and therefore level of intake.…”
Section: Are There Indirect Hormonal Effects On the Brain?mentioning
confidence: 99%
“…While there is virtually no information concerning the roles of these hormones in the expression of seasonality of intake in ruminants, CCK, which is secreted in response to ingestion of food and interacts with sensors in the gut wall (Praissman et al 1983) and pancreas (Steigerwalt & Williams, 1981), was found to act as a satiety factor in ruminants (Farningham et al 1993), with its effects being potentiated by central administration of insulin (Riedy et al 1995;Woods et al 1996). Thus, CCK may be involved in the determination of meal pattern and therefore level of intake.…”
Section: Are There Indirect Hormonal Effects On the Brain?mentioning
confidence: 99%
“…The IC 50 values for the binding of gastrin 17 were slightly higher than the values, which range from 0.94 to 6.4 nM, previously reported for the cloned human CCK2 receptor (Ito et al 1993 ; Lee et al 1993 ; Pisegna et al 1992 ). The affinity of gastrin 17 SO 4 for the cloned human CCK2 receptor does not appear to have been reported previously, but data for binding to dispersed gastric glands from the guinea pig fundus also suggest that sulphation increases the affinity for the CCK2 receptor, in that case by a factor of tenfold, from 16 to 1.6 nM (Praissman et al 1983 ). Binding of gastrin 17 , gastrin 17 SO 4 and gastrin 17 PO 4 to the CCK1 receptor was not detected in our experiments (Fig.…”
Section: Resultsmentioning
confidence: 68%